1999
DOI: 10.1121/1.426740
|View full text |Cite
|
Sign up to set email alerts
|

A long-range and variable focus phase-conjugation experiment in shallow water

Abstract: A second phase-conjugation experiment was conducted in the Mediterranean Sea in May 1997 extending the results of the earlier time-reversal mirror experiment ͓Kuperman et al., J. Acoust. Soc. Am. 103, 25-40 ͑1998͔͒. New results reported here include ͑1͒ extending the range of focus from the earlier result of 6 km out to 30 km, ͑2͒ verifying a new technique to refocus at ranges other than that of the probe source ͓Song et al., J. Acoust. Soc. Am. 103, 3234-3240 ͑1998͔͒, and ͑3͒ demonstrating that probe-source p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
86
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(89 citation statements)
references
References 13 publications
3
86
0
Order By: Relevance
“…The striation pattern is steeper, and while the concept of an invariant remains plausible a larger numerical value is in order. The result is consistent with a recent field experiment where both source and receivers were below the thermocline and ß =1.4 was observed [8].…”
Section: Range-independent Scenariossupporting
confidence: 82%
See 1 more Smart Citation
“…The striation pattern is steeper, and while the concept of an invariant remains plausible a larger numerical value is in order. The result is consistent with a recent field experiment where both source and receivers were below the thermocline and ß =1.4 was observed [8].…”
Section: Range-independent Scenariossupporting
confidence: 82%
“…More recently, the concept has received attention in the Western literature [7]. It was used to move the focal range in a phase conjugation experiment [8]. The theory was extended to environments varying in azimuth and used in the analysis of single receiver spectrograms [9].…”
Section: Introductionmentioning
confidence: 99%
“…In recent times, extensive research has been conducted on time reversal waves (phase conjugate waves) in ocean acoustics [1][2][3][4][5][6][7][8][9][10]. In ocean acoustics, time reversal waves are used as follows: Acoustic waves transmitted from a source are received at the time reversal mirror (TRM) array; these signals are reversed in the time domain (which corresponds to phase conjugate signals in the frequency domain); these time-reversed signals are retransmitted from the TRM array; and they converge to the focus where the original source existed, even in unknown and inhomogeneous media.…”
Section: Introductionmentioning
confidence: 99%
“…This is an important issue since in practical applications the medium properties may change during the experiment [12,15]. Some experimental studies have also shown that the refocused signal is modified as the underlying medium changes [25,34]. Therefore, we analyze time reversal experiments in a slightly different setting than the one described above.…”
Section: Introductionmentioning
confidence: 99%